Importance of pre-operative dialogue in pelvic surgery - Thompson, Leslee (Operating Room Nurses Association of Canada Journal, 1988)
A woman's ability to adjust psychologically and sexually to pelvic surgery depends in part on the type of information she is given prior to going into surgery, the way it is given and the frequency with which it is reinforced.